2014
DOI: 10.9790/0853-131153741
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Caries among Primary School Attendees in Najran-Saudi Arabia

Abstract: The present

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 5 publications
1
12
1
6
Order By: Relevance
“…Also, a study conducted by Elfaki and her colleagues found that most of the respondents had no idea about fluoridated toothpastes [56]. This result however, was much lower than the result obtained by Al-Omiri and his team [59].…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Also, a study conducted by Elfaki and her colleagues found that most of the respondents had no idea about fluoridated toothpastes [56]. This result however, was much lower than the result obtained by Al-Omiri and his team [59].…”
Section: Discussioncontrasting
confidence: 51%
“…Elfaki and her team assessed the impact of health education program on promoting knowledge and practices among school age children in Najran, Saudi Arabia. They found that after the health education program conduction students' knowledge was significantly improved (p<0.01) [56]. The baseline oral health knowledge of the sample was generally por compared to other studies [56,59,60].…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations